Ruin, monument and simulacrum at the University City in Madrid - Salamanca Villamizar, Carlos (Revista de Antropología Social, 2026)
In the context of the Spanish War, the University City of Madrid was the scene of an intense trench battle that contributed to building a long authoritarian period that produced a dense material history of ruins, rubble, monuments and specters that haunt the present. In this contribution we make this territory a device for inquiry into the ways in which Francoism constructed memory and oblivion around its own past. From a material and spatial perspective, we critically analyze the meanings in tension that intersect in this territory from a series of units of different nature and scale, taken as a constellation; models of destruction and utopia, airplanes as monuments and evidence, landscapes produced by reforestation projects, orientalist evocations, imperial trials out of time, monuments of the future. Later we analyze some links between this legacy and memory practices, proposing new lines of approach.